Competitively versus cooperatively? An analysis of the effect of game play on levels of stress. (March 2016) - Roy, Amanda; Ferguson, Christopher J.
Abstract: Many gamers report that playing video games, including those with violent content, helps them to reduce stress. However, few studies have examined competitive and cooperative video game play as they relate to stress reduction. The current study employed a design to acutely stress 100 participants before assigning them randomly to play a mildly violent game either competitively or cooperatively with a female confederate. Results indicated stress levels declined over time at equal levels during both competitive and cooperative game play. Participants in the competitive condition held a slightly less positive impression of the confederate following game play, although players held a generally positive impression of the confederate overall. Highlights: Gamers often report that playing games help reduce stress. Competitive and cooperative gameplay were compared for stress reduction. Both competitive and cooperative gameplay reduced stress. Players in cooperative mode rated a confederate higher than in competitive.